Compartimentos da matéria orgânica do solo, agregação, mecanismos de proteção e sequestro de carbono influenciados pela calagem superficial em sistema plantio direto - Briedis, Clever (2010)
Liming is the most often practice used to neutralize soil acidity, and also promotes chemical changes that can alter the soil organic matter (SOM) pools and the mechanisms of flocculation, formation and stabilization of macro-and microaggregates. The objective of this study was to evaluate carbon sequestration, in the whole and in the aggregates samples, and the changes in the SOM pools affected by liming in a long-term no-tillage. The experiment was conducted in an Oxisol, located in Ponta Grossa, PR. The experimental design was a randomized complete block, arranged as split plot with three replications. The main plot consisted of dolomite lime applied on the soil surface at a 0 or 6 Mg ha-1 in 1993, and 0 or 3 Mg ha-1 in 2000 in plots previously with and without lime, and the treatments was assigned as: 0+0, 6+0, 0+3 and 6+3 Mg ha-1. The subplots were represented by sampling depth and consist of 0-2.5, 2.5-5, 5-10 and 10-20 cm layer. The soil samples were taken in September 2008 and the total organic carbon (TOC) was analyzed in the whole sample, in the aggregates and in the particulate organic carbon (POC) and in the fraction associated with minerals carbon (OCAM). Aggregates of 8-19 mm, in the 0-2.5 cm layer were analyzed by using scan microscope spectrometer X-ray (EDS) for elemental analysis of carbon (C) and calcium (Ca). Liming promoted accumulation of TOC mainly in the layer 0-2.5 cm. The TOC stocks at 0-20 cm were 49.9, 52.9, 52.7 and 57.5 Mg ha-1 for 0+0, 6+0, 0+3, 6 +3 treatments, respectively. Stocks in the SOM fractions were also increased with liming. The increase in POC stock was close relationship (R2 = 0.98, P = 0.011) with the C accumulated input through crop residue, which was higher in plots that were limed. A positive correlation was found between TOC and C extracted in hot water (CHW), total polysaccharides (TP) and labile (LP). Correlations also showed that TOC had a closer relationship with POC than with OCAM, suggesting a greater influence on the labile fraction of TOC increase with liming. In aggregate, the effect of liming in TOC accumulation was mainly in 0-2.5 cm depth. The treatments with liming showed high mean weight diameter (MWD), which provided a large stock of TOC in the 8-19 mm aggregate size. A higest proportion of large aggregates with liming was closely correlated with the TOC content of whole sample. The highest liming dosis resulted in both COP and in OCAM, in the largest class of aggregates. The proportion of POC average of the treatments in relation to OCAM, this class of aggregates, has decreased in depth, and were 18, 13, 10 and 8% at depths of 0-2.5, 2.5-5, 50-10 and 10-20, respectively. Elemental analysis of C and Ca showed a positive correlation of those elements contained in a section of clay from the center of 8-19 mm aggregates. The results suggest that application of lime in soil with clay fraction dominated by kaolinite, brings benefits to structuring and promotes an increase of C in the whole sample and in aggregates.